Letters from Japan's sixteenth and seventeenth centuries correspondence of warlords, tea masters, Zen priests, and aristocrats - Pitelka, Morgan 1972-; Tanimura, Reiko; Masuda, Takashi (Japan research monograph, 2021)
"This book collects twenty-three original, handwritten Japanese letters from the sixteenth and seventeenth centuries and provides transcriptions, translations, and essay commentaries for each. In addition, introductory essays contextualize such letter writing in the politics of the period, the cultural trends of the day, the value of calligraphy, and the history of writing in Japan"--